MOSQUITO CONTROL EMERGENCY PREPAREDNESS AND RESPONSE TO NATURAL DISASTERS - CONNELLY, C. ROXANNE (J Am Mosq Control Assoc, 2020)
On February 9, 2019, the Bipartisan Budget Act of 2018 was signed into law and appropriated $200M in hurricane funding to the Centers for Disease Control and Prevention (CDC) for preparation, response, recovery, mitigation, and other expenses related to the consequences of Hurricanes Harvey, Irma, and Maria. The CDC then awarded, through CDC-RFA-TP18–1802 Cooperative Agreement for Emergency Response: Public Health Crisis Response notice of funding opportunity, $51,136,347 in extramural funding. Funding specific to vector-borne diseases, including intramural and extramural (partners and jurisdictions), was $37,628,235 to Florida, Georgia, Louisiana, Mississippi, Texas, Puerto Rico, and US Virgin Islands. State and territorial funding supported the implementation of conventional and novel mosquito control techniques, training for public health pest control applicators, replacement of mosquito surveillance and control supplies utilized in the aftermath of the 2017 hurricanes, insecticide resistance testing and training, and source reduction. Additionally, the CDC hurricane funding supported this special issue of the Journal of the American Mosquito Control Association (JAMCA) focused on mosquito control response in the wake of natural disasters. We invited hurricane relief funding grantees, mosquito control programs, academics, manufacturers, product distributors, and applicators to submit response plans or descriptive articles related to their experience with mosquito control after natural disasters. The objective of this special issue of JAMCA is to provide a comprehensive volume that includes resources to help guide mosquito control in areas affected by natural disasters. The shared experiences should serve to assist others involved in mosquito control in planning for and responding to natural disasters.